Critical value management activities in building projects: A case of Egypt - Kineber, A.F. (MDPI AG, 2020)
Value management (VM) is one of the principles adopted by stakeholders to manage issues in the building industry. This paper aims to examine VM diffusion between residential building entities in the Egyptian residential building industry. This research was confined to the Cairo and Giza regions, with enough residential building experience from clients, consultants, and contractors. A quantitative questionnaire survey was generated to find answers from those active in the residential building industry. The results show that although VMâs most widely practiced activities in the Egyptian construction industry are only information phase activities, professionals in Egyptian building projects agreed that all VM activities are important. The results also demonstrated that there is a significant positive correlation among VM phases. The results constitute activities for the adoption of VMs in Egypt. Its guidelines will dramatically enhance the implementation of VMs both in Egypt and in other developing countries where similar projects are conducted. Finally, this research strengthens the residential building industryâs present management by enhancing VM tools and elements to generate value for money. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.